Incidence of familial hypercholesterolemia in patients with early manifestations of coronary artery disease: data from a Russian multicenter study and meta-analysis - A. A. Rogozhina; A. O. Averkova; E. A. Zubova; L. O. Minushkina; V. A. Brazhnik; O. N. Ivanova; M. A. Chichkova; N. R. Khasanov; E. D. Kosmacheva; O. I. Boeva; D. A. Zateyshchikov (Российский кардиологический журнал, 2023)
Aim. To assess the possibility of familial hypercholesterolemia (FH) detection among patients with early coronary artery disease (CAD) in practice in comparison with data from different populations. Patients with early manifestations of CAD are a promising group for identifying a proband with FH and subsequent cascade screening. The question remains open about the sufficiency of clinical criteria for diagnosing this disease.Material and methods. We examined 651 patients with CAD manifestations aged £55 years in men and £60 years in women. FH was diagnosed according to the Dutch Lipid Clinic Network (DLCN) criteria, and cardiovascular risk was assessed using the Montreal-FH-SCOR E. In 35 phenotype-positive patients with FH, as well as 5 with lowdensity lipoprotein cholesterol levels ³5,5 mmol/l and 23 with age of manifestation of coronary artery disease £35 years, the coding sequence of the genes for apolipoprotein B (APOB), low-density lipoprotein receptor (LDLR), low-density lipoprotein receptor adapter protein 1 (LDLRAP1), proprotein convertase subtilisin/kexin type 9 (PCSK9).Results. Definite FH was in 8 (1,2%), probable in 27 (4.2%), possible in 339 (52,1%) patients, while 277 (42,5%) patients had DLCN score of <3 points; 31 (88,6%), of 35 phenotype-positive patients had a high Montreal-FH-SCORE risk. Six carriers of pathogenic variants were identified, 2 of which were among phenotype-negative patients. A meta-analysis of 16 studies with 13065 patients (2012-2023) showed that the incidence of FH is 5,22 (4,848-5,619)% (fixed model) and 5,93 (4,528-7,515)% (random model).Conclusion. The use of existing diagnostic scales does not provide guaranteed detection of FH among patients with early CAD. It is likely that DLCN modification by additional gradation of the criterion for the age of CAD manifestation will help increase its diagnostic value.